BS69 is involved in cellular senescence through the p53–p21Cip1 pathway - Zhang, Wei (Nature Publishing Group, 2007)
The multidomain-containing cellular protein BS69 interacts with adenovirus E1A and several other viral and cellular factors, and acts as a transcription repressor. Here, we show that BS69 is involved in the p53–p21Cip1-mediated senescence pathway. Knockdown of BS69 by RNA interference in human primary fibroblasts results in elevated levels of p21Cip1 and the appearance of several senescent markers, including enhanced senescence-associated β-galactosidase activity and formation of senescence-associated heterochromatin foci. Importantly, knockdown of either p53 or p21Cip1, but not p16(INK4a) or Rb, allows cells to bypass premature senescence that is induced by BS69 knockdown. Furthermore, we show that BS69 forms complexes with both p53 and p400, and that BS69 associates with the p21Cip1 promoter through p53. Together, our data indicate that BS69 is involved in cellular senescence mainly through the p53–p21Cip1 pathway.